2019
DOI: 10.1016/j.heliyon.2019.e02571
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the antioxidant-rich xanthone extract from mangosteen (Garcinia mangostana L.) pericarp via microwave-assisted extraction

Abstract: Total phenolic content (TPC) and antioxidant properties of xanthone extract from mangosteen pericarp via microwave-assisted extraction (MAE) method was optimized by response surface methodology (RSM). The MAE extraction conditions to obtain optimum antioxidant-rich xanthone extract were at 2.24 min of irradiation time, 25 mL/g of solvent-to-solid ratio and 71% of ethanol concentration. The predicted results for four responses were as follows; 320.31 mg gallic acid equivalent/g extract, 83.63% and 93.77% inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 32 publications
1
32
0
2
Order By: Relevance
“…The lowest phenolic content, found in mango peel extract (MG-MAE-W), was only 4.82 ± 0.38 mg GAE/g DM. In previous studies, the phenolic content in mangosteen peel was between 5 and 320 mg GAE/g DM [ 14 , 15 ]. A higher amount of phenolic content obtained from rambutan peel was 100–760 mg GAE/g DM [ 1 ], whereas the phenolic content in mango peel depended on cultivars in a range of 0.285–5.742 mg GAE/g DM [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest phenolic content, found in mango peel extract (MG-MAE-W), was only 4.82 ± 0.38 mg GAE/g DM. In previous studies, the phenolic content in mangosteen peel was between 5 and 320 mg GAE/g DM [ 14 , 15 ]. A higher amount of phenolic content obtained from rambutan peel was 100–760 mg GAE/g DM [ 1 ], whereas the phenolic content in mango peel depended on cultivars in a range of 0.285–5.742 mg GAE/g DM [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The previous study, optimizing the conditions of extracting mangosteen peel by MAE, found that 60% ethanol in water was suitable. It is possible that the addition of water into ethanol increases the polarity and thus reduces the ratio of water in the mixture of water and ethanol, resulting in the higher yield of phenolic content [ 14 ]. However, there were other factors that might influence the phenolic content such as pretreatment process, types of solvent, solid–solvent ratio, particle size of sample, extraction time, solvent mixture ratio and variation in plant materials such as season, aging and cultivation.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the solid‐solvent ratio from 1:10 to 1:17 g/ml, it can be seen that the yields are elevating from 171 to 328 mg GAE/g for TPC and from 210 to 403 mg QE/g for TFC (Figures 2a, 3a). This could be because, the higher amount of solvent volume enhances the phenolic compound yield as the mass transfer of solute present in the sample into solvent medium takes place (Karunanithi & Venkatachalam, 2019; Mohammad et al, 2019). This sufficient solvency result could be related to previous results of Alara and Abdurahman (2019).…”
Section: Resultsmentioning
confidence: 99%
“…This contradiction may also be attributed to the fact the amount of total xanthone in the mangosteen pericarp extract is strongly affected by the extraction capacity of the solvent to recover different phenolic constituents from various fruit origins, as well as the methods of transportation and storage [40][41][42]. Aisha, Abu-Salah & Ismail [43] have reported that toluene is the most e cient extraction solvent for mangosteen pericarp extract compared to 75% ethanol and methanol [44].…”
Section: Discussionmentioning
confidence: 99%